Avaliação de elemento filtrante à base de quitosana na aquicultura - Zadinelo, Izabel Volkweis (2018)
Closed water recirculation systems in aquaculture depend on filter areas that keeps water quality to crop aquatic organisms. Chitosan is a biopolymer obtained by chitin deacetylation from the shell of crustaceans. It has adsorbent characteristics and can be used in cropping water treatment. Chitosan foam is composed of chitosan and neutral emulsifier, and it is malleable. Thus, this study aimed at evaluating chitosan foam as a filter element for aquaculture pollutants in synthetic solutions, making a filter, testing its use in closed recirculation systems for water quality maintenance during Nile tilapia cropping at two volume scales of tanks (two trials: Trial 1: 35 L tanks; Trial 2: 130 L tanks), checking its effects on zootechnical and histopathological performance of gills and hepatopancreas of fish, and finally evaluating its digestibility in diets of Nile tilapia. The best dosage of foam in filter to adsorb pollutants in synthetic solutions was 0.10 (% m v-1), with maximum removal of 32.8% ammonia, 57.2% nitrite, 89.5% % dissolved orthophosphate and 99.9% turbidity. This dosage was then used in filters of three individual water recirculation systems during Nile tilapia cropping in Trials 1 and 2 (Trial 1: 35 L tanks; Trial 2: 130 L tanks) and compared the results of water quality, zootechnical performance and histopathology of gills and hepatopancrea, with those obtained in tanks of the other three recirculation systems by using biological filters with bioballs. During the experimental term of trial 1 and trial 2, it was observed that the use of filter with chitosan foam in cropping tanks in water recirculation systems resulted in lower or equal concentrations of total ammonia, nitrate and dissolved orthophosphate, remained with the same or higher alkalinity than in biologically bioball filtered tanks. There were no statistical differences in final weight, feed conversion and survival among treatments (p> 0.05) in both trials, and in the organ index (Iorg) in trial 2. It is recommended to exchange chitosan foam every 30 days of cropping. After removing the filters, chitosan foam can be used in diets of cropped fish to avoid discarding them. The determination of apparent digestibility was carried out by the indirect fecal collection method (Nile tilapia with average weight of 50 ± 5 g), using chromic oxide as an inert indicator, diet as reference and test diet (70% reference diet and 30% chitosan foam). Chitosan foam showed 83.7% digestible dry matter, 5.7% digestible protein, 7.9% digestible fat, 0.6% digestible ashes, 17.6% of digestible crude fiber and 1,021 kcal kg-1 of digestible energy, which was partially digestible for Nile tilapia and can be used mainly as a food source of fiber and fat. Chitosan foam is efficient in keeping water quality in closed recirculation systems during Nile tilapia cropping, and it can be included in fish diets to end a sustainable cycle of the aquaculture chain.